Color signless Laplacian energy of graphs - Pradeep G. Bhat; Sabitha D’Souza (AKCE International Journal of Graphs and Combinatorics, 2017)
In this paper, we introduce the new concept of color Signless Laplacian energy . It depends on the underlying graph and the colors of the vertices. Moreover, we compute color signless Laplacian spectrum and the color signless Laplacian energy of families of graph with the minimum number of colors. The color signless Laplacian energy for the complement of some colored graphs is also obtained.